Aspectos bucais da síndrome de Rubinstein-Taybi: relato de dois casos clínicos - Barros, Fabiana Mesquita; Iida, Letycia; Alves, Thais Dutra; Castorino, Aparecida Angélica; Martins, Fabiana; Gallotini, Marina (Clinical and Laboratorial Research in Dentistry, 2018)
Rubinstein-Taybi syndrome is a rare genetic multisystem disorder characterized by typical facial dimorphism, slow growth, mental deficiency, and multiple dental abnormalities. This case report describes the oral-facial findings of Rubinstein-Taybi syndrome affecting a 11-year-old Brazilian male, and a 10-year-old female. The oral findings of the patients, such as thin upper lips, prolonged retention of the primary teeth, and hypodontia are reported, and the clinical management is discussed.